Atrial fibrillation and atrial tachycardia in patients with chronic thromboembolic pulmonary hypertension treated with pulmonary endarterectomy. (15th July 2020) - Havranek, Stepan; Fingrova, Zdenka; Ambroz, David; Jansa, Pavel; Kuchar, Jan; Dusik, Milan; Lindner, Jaroslav; Kunstyr, Jan; Aschermann, Michael; Linhart, Ales
Abstract: Atrial fibrillation (AF) and atrial tachycardia (AT) are frequently observed in patients with chronic thromboembolic pulmonary hypertension (CTEPH) who were treated with pulmonary endarterectomy (PEA). Their prevalence and impact on prognosis of patients are not known. We analysed the prevalence of AF/AT and the clinical outcome in 197 patients with CTEPH treated with PEA (median age 62; interquartile range 53–68 years; 62% males). The prevalence of AF/AT was 29% (57 patients). Compared to patients without arrhythmia, the subjects with AF/AT were older [60 (50–67) vs. 62 (57–70) years], manifested an increased size of the left atrium [39 (35–44) vs. 45 (40–50) mm], had a reduced 6-min walking distance [411 (321–506) vs. 340 (254–460) m], and higher pulmonary artery systolic pressure after PEA [38 (30–47) vs. 45 (38–71) mmHg], all results with P -value <0.05. During the follow-up with a median 4.2 (1.6–6.3) years, 45 (23%) patients died. In a multivariate Cox regression model only the male gender [hazard ratio (HR) 2.27, 95% confidence interval (CI) 1.15–4.50], a reduced 6-min walking distance (HR 3.67, 95% CI 1.74–7.73), and an increased New York Heart Association class (HR 8.56, 95% CI 4.17–17.60) were associated with mortality ( P < 0.05). The prevalence of AF/AT in patients with CTEPH treated with PEA is high. Arrhythmias are associated with reduced functional capacity but not with mortality.